The Relation Between Flor’s Taxonomy and Trosborg’s Modification in Giving Suggestions in Students’ Spoken Presentation - Dwiyanto, Agus; Rukmini, Dwi; Widhiyanto, Widhiyanto (English Education Journal, 2021)
Considering the intense presentation activity in the graduate classroom, the use of suggestion turns to be primary in delivering points. This triggered the researchers to study the issue. The primary objective of this study is to explain the relation between Flor’s (2005) suggestion taxonomy and Trosborg’s (1995) suggestion modification through the realization of speech acts of suggestion. The study applied a descriptive qualitative research method in which the data were gathered by using Oral Discourse Completion Task (ODCT). The participants of the study were 15 EFL students of a graduate program of a university in Semarang. The responses then were analyzed based on Flor’s (2005) suggestion taxonomy and Trosborg’s (1995) suggestion modification coding scheme. The results revealed that there were 146 suggestions produced. Conventionalized forms were realized more frequently than other Flor’s taxonomies. Furthermore, negative imperative was the most used indirect strategy. The subjects realized more specific formulae of the most in conventionalized forms. The indirect strategy was realized equally. Politeness marker was used more frequently while grounder claimed the highest findings in external modification. The relation between the taxonomy and modification showed that direct taxonomy and external modification was the highest relation found in the suggestion realization. It is expected that this research can give profound contributions to university students, English teachers, and other fellow researchers to develop further research related to suggestion speech acts. At last, it is suggested that English teachers particularly are to raise EFL learners’ pragmatic awareness by implementing appropriate teaching approach and method.